Citronella suaveolens, a new generic record for Vietnam, with a key to Vietnamese Cardiopteridaceae - Nuraliev, Maxim S.; Schori, Melanie; Tagane, Shuichiro; Kuznetsov, Andrey N.; Kuznetsova, Svetlana P.; Utteridge, Timothy M.a. (Phytotaxa, 2022)
Citronella suaveolens is reported from Quang Nam Province in southern Vietnam, representing the first record of this species and the genus Citronella in the country and in mainland Southeast Asia in general. Detailed photographic illustrations of studied specimens are provided. A key to the Vietnamese genera and species of Cardiopteridaceae is presented. Diversity of Citronella in the Malesian region is discussed. Floristic affinities of Malesia and Eastern Indochina are highlighted by a list of illustrative examples.